Expanding the Scope of Nickel-Catalyzed Carbon-Oxygen Bond Activation: Towards the Employment of Easily Accessible Chemicals in Modern Catalysis - Cook, Adam (Université d'Ottawa | University of Ottawa, 2024)
The field of transition metal catalysis has exploded, both in popularity and utility, over the course of the past half-century. Into modernity, chemists have sought to improve methods for the transition metal-catalyzed activation of increasingly strong bonds, leading to the emergence of the subfield of carbon-oxygen bond activation. Carbon-oxygen bonds are extraordinarily prevalent in the natural world, and unlocking methods to activate them will prove paramount in the push towards a greener, bio-based economy. Nickel has emerged as a privileged, sustainable transition metal catalyst for carbon-oxygen bond activation. This dissertation will focus on the development of methods to expand the boundaries of nickel-catalyzed carbon-oxygen bond activation. After a detailed introduction, chapter two of this dissertation will explore the defunctionalisation of chemical compounds via a process which will be called deoxygenative reduction - installing carbon-hydrogen bonds where once there were carbon-oxygen. Utilizing a nickel catalyst alongside an abundant, inexpensive hydride source, the development of a method that enables the reduction of carbon-oxygen bonds found in esters, ketones, aldehydes, epoxides, ethers, and alcohols will be described. Primary, secondary, and tertiary carbon-oxygen bonds each prove reducible when present in π-activated and non-π-activated positions. Applications of this method are demonstrated towards catalytic deuteration and the reductive defunctionalization of complex molecules including NSAIDs, cholesterol, quinine, and biomass derivatives. The ability of this method to activate carbon-oxygen bonds in tertiary, non-π-activated positions lays the foundation for chapter three, wherein attention will be turned towards the realm of functionalization. This chapter explores the discovery and development of a deoxygenative Suzuki-Miyaura arylation that uses unprotected, non-π-activated alcohols as substrates. Once more, nickel catalysts prove uniquely capable of achieving this reaction, this time being employed alongside Lewis acid catalysts and organoboron coupling partners to forge synthetically valuable C(sp³)-C(sp²) bonds. Yet, this chapter concludes with unanswered questions regarding the nature of the active catalyst, the mechanism of transformation and the substrate scope restrictions. Solutions to these questions form the basis for chapter four, wherein the β-silicon effect - a known phenomenon in physical organic chemistry - is exploited to overcome the limitations of the nickel-catalyzed deoxygenative Suzuki-Miyaura arylation presented in chapter three. A deeper understanding as to how this reaction works is obtained by systematically studying ligand effects and gathering evidence to support the existence of a key carbocation intermediate. This chapter also documents the isolation, characterization, and evaluation of a series of nickel complexes, shedding light on the role of a newly discovered ligand in achieving reactivity. With the development of a method for the Suzuki-Miyaura arylation of non-π-activated alcohols in the rear-view mirror, chapter five describes efforts to employ non-π-activated alcohols in other transformations. A high-throughput approach is taken to explore the chemical space of this transformation, keeping the substrate and catalytic conditions constant while varying the nucleophilic coupling partner. Efforts in achieving the formation of C(sp³)-C(sp³), C(sp³)-C(sp) and C(sp³)-N bonds will be documented.
Keywords: organic chemistry; transition metal; synthesis; catalysis